2019
DOI: 10.1101/519975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

O-GlcNAc transferase suppresses necroptosis and liver fibrosis

Abstract: Over a billion people suffer from chronic liver diseases worldwide, which often leads to fibrosis and then cirrhosis. Treatments for fibrosis remain experimental, in part because no unifying mechanism has been identified that initiates liver fibrosis. Here we report that O-linked β-N-acetylglucosamine (O-GlcNAc) modification protects against hepatocyte necroptosis and initiation of liver fibrosis. Decreased O-GlcNAc levels were seen in patients with liver cirrhosis and in mice with ethanol-induced liver injury… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 54 publications
3
16
0
2
Order By: Relevance
“…These data are consistent with previous studies by Zhang et al demonstrated that OGT deletion, in the liver using a CRE governed by the albumin promoter, resulted in significant necroptosis and fibrosis (7). They further showed that RIP3K undergoes O-GlcNAcylation which reduces the stability of the protein (7). Our studies showed that delayed cell death in OGT-KO mice after PHX is both necroptosis as well as apoptosis (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These data are consistent with previous studies by Zhang et al demonstrated that OGT deletion, in the liver using a CRE governed by the albumin promoter, resulted in significant necroptosis and fibrosis (7). They further showed that RIP3K undergoes O-GlcNAcylation which reduces the stability of the protein (7). Our studies showed that delayed cell death in OGT-KO mice after PHX is both necroptosis as well as apoptosis (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…These data indicate that loss of O-GlcNAcylation may make hepatocytes more vulnerable to cell death. These data are consistent with previous studies by Zhang et al demonstrated that OGT deletion, in the liver using a CRE governed by the albumin promoter, resulted in significant necroptosis and fibrosis (7). They further showed that RIP3K undergoes O-GlcNAcylation which reduces the stability of the protein (7).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other direct evidence for a role of protein O-glycosylation in the silencing of retrotransposon comes from studies of a liverspecific deletion of Ogt in mice (32). We reanalyzed the RNAseq data from this study for transposon reactivation.…”
Section: Targeted Deglcnacylation Reactivates Methylated Transposablementioning
confidence: 99%
“…Polyphenolic compounds silibinin and curcumin reduce NAFLD/NASH and protein O -GlcNAcylation in mouse models [ 56 , 57 ]. In contrast, decreased protein O -GlcNAcylation in human cirrhotic livers and the protective effects of hepatocyte-OGT on alcohol-induced cirrhosis in mice have also been demonstrated [ 58 ]. Overall, both activation and disruption of protein O -GlcNAcylation have been shown to stimulate HSC activation [ [59] , [60] , [61] ].…”
Section: Discussionmentioning
confidence: 99%